EIB Group activities in EU cohesion regions 2022 - EUROPEAN INVESTMENT BANK (European Investment Bank, 2023)
This report analyses the EIB Group's activity in cohesion regions in 2022. This year's edition focuses on the Group's contribution towards innovation for an inclusive, green and digital transition in line with the Innovation, Digital & Human Capital (IDHC) Orientation 2021-2027. The report starts with a review of recent economic trends in cohesion regions and their investments in innovation, followed by a presentation of the EIB Group's activities in these regions in 2022. The Group's support for economic, social and territorial cohesion is presented in relation to policy objectives, activity sectors, countries, contribution to the UN's Sustainable Development Goals (SDGs) and sector-specific project results. A number of case studies are used to illustrate the Group's activities and impact. The wider macroeconomic impact of the Group in cohesion regions is then discussed through the lens of a recent academic study. Finally, the role of digitalisation and innovation in cohesion regions is presented along with the range of tools deployed by the Group to support these policy objectives in cohesion regions.